Comprehensive Assessment of Municipal e-Government Systems in Eastern Ukraine - Volodymyr STRELTSOV; Artem SERENOK; Ewa MATUSKA (Communications of International Proceedings, 2021)
Municipalities increasingly active role during the time of building informational society patterns has drawn further attention to e-governance initiatives on regional and sub-regional levels. The crucial question for both academic and policy-making communities is: are local e-government monitoring tools for post-communist countries adequate for measuring progress in building truly effective, responsive and accountable local self-government with proper level of information security? On the basis of evolving monitoring practices some recommendations are proposed on how to improve the e-governance maturity in eastern Ukraine.
Keywords: Municipalities; Administrative Services; E-Government; E-Administration; Monitoring; Assessment.